On Morrison - Serpell, Namwali, 1980- (Hogarth, 2026)
"Toni Morrison, Nobel Laureate and one of our most beloved writers, has inspired generations of readers. But her artistic genius is often overshadowed by her monumental public persona, perhaps because, as Namwali Serpell puts it, "she is our only truly canonical black, female writer-and her work is highly complex." In On Morrison, Serpell brings her unique experience as both an award-winning writer and professor who teaches a course on Morrison to illuminate her masterful experiments with literary form. This is Morrison as you've never encountered her before, a journey through her oeuvre-her fiction and criticism, as well as her lesser-known dramatic works and poetry-with contextual guidance, archival discoveries, and original close readings. At once accessible and uncompromisingly rigorous, On Morrison is a primer not only on how to read one of the most significant American authors of all time, but also on how to read great works of literature in general. This dialogue on the page between two black women artist-readers is stylish, edifying, and thrilling in its scope and intelligence"-- Provided by publisher.